PENGEMBANGAN INSTRUMEN EVALUASI PENDIDIKAN AGAMA ISLAM PADA RANAH KOGNITIF, AFEKTIF, DAN PSIKOMOTORIK PESERTA DIDIK - Achmad Rasyid Ridha; Mustamik; Gholib Assalam (Lembaga Pengembangan Inovasi Pendidikan Baiturrahman, 2026)
Evaluation of Islamic Religious Education (PAI) learning needs to encompass the cognitive, affective, and psychomotor domains so that student learning outcomes can be measured comprehensively. However, PAI evaluation has so far been dominated by cognitive assessment. This study aims to develop an Islamic Religious Education (PAI) evaluation instrument that encompasses all three domains. The study used a Research and Development (R&D) approach through the stages of needs analysis, instrument design, expert validation, and limited trials at Muhammadiyah 9 Junior High School, Ngemplak, Boyolali. The instruments developed included a written test for the cognitive domain, a questionnaire and observation sheet for the affective domain, and a performance assessment rubric for the psychomotor domain. Validation results indicated that the instrument has a high level of validity and reliability and is suitable for use in Islamic Religious Education (PAI) learning evaluation. This instrument is expected to help teachers conduct more comprehensive learning evaluations oriented toward developing student competencies and character.